Changes in Distortion Product Otoacoustic Emission Caused by Contralateral Broadband Noise - OZIMEK, Edward; WICHER, Andrzej (Archives of Acoustics, 2014)
The main purpose of this investigation was to measure the effect of contralateral acoustic stimulation (CAS) on distortion product otoacoustic emission (DPOAE) in twenty human ears, for a ratio of primary tones $f_2/f_1$ = 1.22 and a wide frequency range of $f_2$ (1.4–9$\,$kHz), for two intensity levels of primary tones ($L_1$ = 60$\,$dB$\,$SPL; $L_2$ = 50$\,$dB$\,$SPL and $L_1$ = 70$\,$dB$\,$SPL; $L_2$ = 60$\,$dB$\,$SPL) and two intensity levels of CAS (50 and 60$\,$dB$\,$SPL). It was found that in the presence of CAS, in the majority of cases the DPOAE level decreased (suppression), but it might also increase (enhancement) or remain unchanged depending on the frequency. The mean suppression level of the component of the frequency $f_{DP} = 2f_1 − f_2$ might be approximated by a linearly decreasing function of the $f_2$ frequency of primary tones. The slope of this function was negative and increased with an increase of the contralateral stimulation level. The higher was the contralateral noise level the greater was the suppression. For the $f_{DP}$ level below about 15$\,$dB$\,$SPL, suppression was observed in a substantial number of measurement cases (in about 85% of all measured cases on average). When the $f_{DP}$ level was higher than 15$\,$dB$\,$SPL, only suppression (not enhancement) was observed.